PENGARUH BAURAN PROMOSI TERHADAP VOLUME PENJUALAN COFFE SOLONG ULEE KARENG BANDA ACEH - Zenitha Maulida; Nurbismi Nurbismi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2022)
The current phenomenon is the lack of a promotional mix strategy carried out by Solong Kopi Ulee Kareng Banda Aceh in order to increase public interest or potential consumers to come and buy the products marketed by Solong Kopi Ulee Kareng Banda Aceh. The purpose of this study was to determine the effect of the promotion mix on sales volume at Coffe Solong Ulee Kareng Banda Aceh. The location of this research was conducted at Solong Kopi Ulee Kareng Banda Aceh, while the object of this research was about the effect of the promotion mix on sales volume at Solong Kopi Ulee Kareng Banda Aceh. The data analysis method used in this research is simple linear regression. The number of respondents in this study were 33 employees with a census sampling technique, where the entire population had the opportunity to be a sample. The results of the study prove that customer satisfaction has an effect on customer loyalty with a t-count value of 11.201, while t-table is 2.039, the results of this calculation indicate that t-count > t-table with a significance of 0.000 or the probability is far below ᵅ = 5%, this implies that The higher the promotion mix, the higher the sales volume will be.